Design and Evaluation of an Inclusive Autonomous Vehicle User Interface Developed for Persons with Visual Acuity Loss - Angeleska, E.; Aleksovska, A.; Avramov, N.; Sidorenko, S.; Rizov, T.; Jankovic, A. (Cambridge University Press (CUP), 2022)
AbstractThis research focuses on evaluating a user interface (UI) for an autonomous vehicle (AV) with the goal to determine the most suitable layout for persons with visual acuity loss. The testing procedure includes a Wizard of Oz AV for simulating an automated ride. Several participants are included in the study and the visual impairments are simulated by specially designed glasses. The conclusions help to determine the optimal graphic design of the UI that can be independently used by persons with blurred vision. The results can be applied to improve the inclusiveness and ergonomics of vehicle UIs.